Epileptiform EEGs and Attention Deficit Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The electroencephalograms (EEGs) of 176 children with attention deficit-hyperactivity disorder (ADHD) were analyzed at the University of Illinois, Chicago.